1971
DOI: 10.1021/ja00731a063
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of sulfur atoms. XII. Arrhenius parameters for the addition to olefins and acetylenes

Abstract: The reactions of ground-state (3P2,i,o) atoms of the group Via elements with olefins have received considerable attention in recent years.1-7 Atomic oxygen yields epoxides, the isomeric carbonyl compounds, and various fragmentation products. Sulfur, selenium, and tellurium give only the cyclic adduct which, with the latter two elements, has only transient existence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 1 publication
(2 reference statements)
2
16
0
Order By: Relevance
“…constant agrees well with the recently published value11 of (7.2 ± 1) X 10s 1. mol-1 sec-1. The rate constants relative to that of ethylene are in satisfactory agreement with the values obtained from the relative Arrhenius parameters determined from conventional photolysis studies 4.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…constant agrees well with the recently published value11 of (7.2 ± 1) X 10s 1. mol-1 sec-1. The rate constants relative to that of ethylene are in satisfactory agreement with the values obtained from the relative Arrhenius parameters determined from conventional photolysis studies 4.…”
supporting
confidence: 80%
“…(2) Considerable broadening of the pmr signal of the a-and b-methyl protons of 1 and 2 are observed in the DNA complex at 32°. 4 In the case of DNA-2 complex the pmr signal of the c-methyl protons is completely broadened and indistinguishable from base-line noise at 32 and 58°, indicating a restricted tumbling rate of the 4-nitroaniline ring of 2. At 90°, where melting of the DNA helix has occurred,5 sharp resonance lines characteristic of the free reporter molecules are observed for the a-, b-, and c-methyl protons. "…”
mentioning
confidence: 93%
“…The two data sets together hint at a curved Arrhenius plot. The earliest measurements [4][5][6] are ca. three times higher than these two studies at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Early measurements of reaction were made at room temperature . The experiments by Davis et al at Ar pressures of 67–530 mbar revealed no pressure dependence for k 1 at 298 K and characterized k 1 over 218–442 K mainly at 133 mbartruerightk1=left(7.13±0.74)×1012leftprefixexp()6.6±0.30.28em kJ 0.28em mol 1/italicRT cm 30.16em molecule 10.16emnormals1…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation